Respuestas
Respuesta dada por:
4
x + y = 12 x - y = 2
x = 12 - y (1) x = 2 + y (2)
↑-------------------------------↑
igualamos
12 - y = 2 + y
-y - y = 2 - 12
-2y = -10
y =
= 5
Luego reemplazamos y=5 en (1)
x = 12 - y
x = 12 - 5
x = 7
x = 12 - y (1) x = 2 + y (2)
↑-------------------------------↑
igualamos
12 - y = 2 + y
-y - y = 2 - 12
-2y = -10
y =
Luego reemplazamos y=5 en (1)
x = 12 - y
x = 12 - 5
x = 7
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años